"Los vampiros del pueblo" (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2021)
The study analyses the play Los vampiros del pueblo (1904) by Niceto Oceta (1864-1933) in the context of contemporary anticlerical literature, focusing on journalistic and literary controversies.
Keywords: 20th Century Spanish Theatre; Niceto Oceta; Vampires, Anticlericalism